Integrating Deep Learning to Enhance Collaboration Skills Among Elementary School Students: Challenges and Opportunities - Lutfiana Nurohmah; Indriani Nur Amanah; Junia Amalia; Kumala Wahyu Widowati; Melata Warisma; Muhammad Rafli; Brigida Intan Printina (International Journal of Education, Language, and Social Science, 2026)
Collaboration skills represent a crucial 21st-century competence integrated through the mutual cooperation (gotong royong) dimension of the Pancasila Student Profile. However, empirical evidence indicates that the collaborative abilities of elementary school students in Indonesia remain considerably low. While previous studies have extensivelyl focused on field-based interventions, there remains a critical gap in comprehensively synthesizing the theoretical rediness and systemic hurdles of shifting traditional paradigms toward deeper learning models in the Indonesian context. This study aims to examine the concept of collaboration skills, analyze the contribution of the deep learning approach to strengthening students' cooperative character, and map the challenges and opportunities of its implementation in elementary schools. The research method employed is library research utilizing content analysis techniques on reputable academic literature published within the last ten years. The findings indicate that the deep learning approach, anchored on mindful, meaningful, and joyful learning principles, holds the potential to transform the classroom climate into a student-centered environment, which may facilitate enhanced social interaction, empathy, and shared responsibility. The primary opportunity of this approach lies in its capacity to shift the traditional memorization paradigm toward holistic conceptual understanding through concrete activities such as Project-Based Learning (PjBL) and interactive learning. Nevertheless, systemic challenges persist, including limited teacher pedagogical capacity, rigid administrative burdens, disparities in digital infrastructure, and the heterogeneity of students' academic backgrounds, which risk inducing cognitive overload. This study concludes that strengthening deep learning-based collaboration requires holistic policy interventions, continuous teacher professional development, and the provision of authentic affective assessment instruments.